Acquired Torticollis in Children: A Clinical Manifestation with a Broad Spectrum of Severity - Correia, Laura (2024)
Acquired torticollis in children is a clinical manifestation with a wide etiological spectrum, which ranges from traumatic, infectious or inflammatory processes, to non-musculoskeletal entities of neurological, tumoral or even ophthalmological origin. It can constitute the form of presentation of benign and self-limiting processes, as well as progressive and potentially fatal conditions, so the identification of alarm signs, in the collection of the clinical history and in the performance of the objective examination of the child, is mandatory. It is also essential for the differential diagnosis to distinguish between intermittent (paroxysmal) or persistent torticollis over time, as well as verifying the variation in its laterality and the recurrence of episodes. We present an illustrative clinical case of torticollis of tumor etiology, in a female child, aged 16 months, with a prolonged clinical picture, in need of interdisciplinary evaluation and complementary investigation, to define a diagnosis and a targeted therapeutic strategy.